A systematic review on risk factors associated with sepsis in patients admitted to intensive care units. Issue 2 (March 2019) - Fathi, Mohammad; Markazi-Moghaddam, Nader; Ramezankhani, Azra
Abstract: Objective: We sought to systematically review data on the risk factors influencing the incidence of sepsis in patients admitted to intensive care units (ICUs). Review methods: An electronic search was undertaken in PubMed, MEDLINE, Scopus, and the Cochrane Library for studies reporting the risk factors of sepsis from the earliest available date up to December 30, 2016. Results: Among the 2978 articles, 14 studies met the inclusion criteria with a total of 56 164 participants from nine countries. The extracted risk factors were from the following categories: demographic, critical care interventions, surgery-related factors, pre-existing comorbidities, severity of organ injury, and biomarkers and biochemical and molecular indicators. From demographic factors, older age and male gender were associated with an increased risk of sepsis among ICU-admitted patients. Conclusion: Our analysis comprehensively summarised the risk factors of sepsis in patients admitted to medical, surgical, neurologic, trauma, and general ICUs. Age, sex, and comorbidities were non-modifiable risk factors; however, critical care interventions and surgery-related factors were modifiable factors and suggest that improving the care of surgical patients and effective management of critical care interventions may play a key role in decreasing the development of sepsis in patients admitted to the ICUs.